High resolution numerical modelling of the atmosphere and ocean - Hamilton, Kevin, 1956-; Ohfuchi, Wataru, 1963- (Springer, 2008)
"This book includes 15 individual papers that highlight the emerging research in atmospheric and oceanic science that has been made possible by exploiting newly available computational resources. Results from regional atmospheric, global atmospheric, global ocean, and global coupled ocean-atmospheric models are discussed in the various contributions."--Jacket.